PENENTUAN LOKASI TEMPAT EVAKUASI AKHIR PENGUNGSI PADA ANCAMAN BENCANA TSUNAMI KOTA PADANG - Rafiqa Fijra (Jurnal Teknosains, 2018)
Padang is capital city of West Sumatera whose coastal layout and approximately 50% of population live in low area. It opposites to the Indian Ocean which near the Megathrust subduction which can trigger a powerful earthquake and generate tsunami. Because of the potential risk, important to finding the final evacuated region (TEA) location addressed by evacuee of each affected village, and defining the evacuee population and its susceptive population on each TEA. Defining the location TEA is provided by formulating the linear programming model which minimizing the total traveled distance. Then, defining of population and susceptive of evacuee in each TEA also analyzed to support the response disaster occurred. The optimization model is conducted in three level scenarios of tsunami scale, that are big, medium, and small .